The Effect of Hypoxic and Hyperoxic Training on Certain Blood Cells, Blood Gases, and Time Trial Performance of Cyclists - Ali Jamil Zghair (Cuestiones de Fisioterapia, 2025)
The study is aimed to prepare Preparing hypoxic exercises (oxygen deficiency) for the first experimentalgroup competitors and hypoxic exercises (oxygen increase) for the second experimental groupcompetitors, and identifying the superiority of the differences between the measurements and posttests of the first experimental group (oxygen deficiency) and the second experimental group (oxygenincrease) in the values of some blood cells (EPO, FERs, Hb, (Hct, and gas exchange (po2, spo2) and theachievement of the individual race against the clock for the Dhi Qar Cycling Federation racers amongthe research sample members.